Heat shock-mediated cell cycle blockage and G1 cyclin expression in the yeast Saccharomyces cerevisiae. - Rowley, A (1993)
For cells of the yeast Saccharomyces cerevisiae, heat shock causes a transient inhibition of the cell cycle-regulatory step START. We have determined that this heat-induced START inhibition is accompanied by decreased CLN1 and CLN2 transcript abundance and by possible posttranscriptional changes to CLN3 (WHI1/DAF1) cyclin activity. Persistent CLN2 expression from a heterologous promoter or the CLN2-1 or CLN3-1 alleles that are thought to encode cyclin proteins with increased stability eliminated heat-induced START inhibition but did not affect other aspects of the heat shock response. Heat-induced START inhibition was shown to be independent of functions that regulate cyclin activity under other conditions and of transcriptional regulation of SWI4, an activator of cyclin transcription. Cells lacking Bcy1 function and thus without cyclic AMP control of A kinase activity were inhibited for START by heat shock as long as A kinase activity was attenuated by mutation. We suggest that heat shock mediates START blockage through effects on the G1 cyclins.